2011
DOI: 10.1177/1045389x10392610
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Hysteresis Compensation in a Thin SMA Wire Using ANFIS Methods

Abstract: Having a responsive behavior to applied voltage/current, shape memory alloy (SMA) wires are widely used as miniature, low mass, compact actuators for many applications. Due to the non-linear hysteretic behavior, SMA wires require advanced control techniques for precision control when used as actuators. In this article, an adaptive neuro-fuzzy inference system (ANFIS) is developed to compensate for the hysteretic non-linearity in a thin SMA wire. An experimental setup is designed to test the SMA wire, which can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…For example, a Preisach model was employed for current-strain hysteresis of an SMA actuator [11], but under a constant tension force. An adaptive neuro-fuzzy inference system model was realized for an SMA actuator at various frequencies, but only the voltage -strain hysteresis was captured [12]. Similarly, a generalized Prandtl-Ishlinskii model was adopted for position control, only the temperature-deflection hysteresis was compensated [13].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a Preisach model was employed for current-strain hysteresis of an SMA actuator [11], but under a constant tension force. An adaptive neuro-fuzzy inference system model was realized for an SMA actuator at various frequencies, but only the voltage -strain hysteresis was captured [12]. Similarly, a generalized Prandtl-Ishlinskii model was adopted for position control, only the temperature-deflection hysteresis was compensated [13].…”
Section: Related Workmentioning
confidence: 99%
“…It was found that the control accuracy of the proposed compensation algorithm was not higher than existing methods. This can be explained as follows: Firstly, a predominant class of the existing studies focused on two-dimensional hysteresis while holding the third-dimensional property as a constant [11][12][13]18]. Although accurate characterization and compensation were achieved, these models could not work for many practical cases where the third-dimensional property also changes.…”
Section: Inverse Compensationmentioning
confidence: 99%
“…Recently, intelligent methods such as neural networks and fuzzy logic system provide a new way to model hysteresis (Li et al, 2013; Ma et al, 2015; Mai et al, 2016; Wang et al, 2018; Zhang and Tan, 2010). Kilicarslan et al (2011) developed an adaptive neuro-fuzzy inference system (ANFIS) for hysteresis modeling. Xu and Zhou (2017) proposed the identification method of KP hysteresis model based on Elman neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…Having the capability of combining the fuzzy decision making and ANN learning, ANFIS architectures are useful tools for representing non-linear systems for control applications. In [15,16], the authors use an ANFIS architecture to model the hysteretic response and train an inverse ANFIS controller which utilises the desired output as the controller input and provides the appropriate control action. Having the feed-forward inverse controller combined with a PI controller, the control approach is capable of compensating the hysteretic behaviour of the system and can successfully track a reference trajectory.…”
Section: Introductionmentioning
confidence: 99%